Effect of ART on anemia in Children living with HIV attending tertiary care hospitals of New Delhi - Verma, D; Acharya, A S; Bachani, D; Seth, A; Hemal, A (Indian Journal of Community Health, 2014)
Background: Globally in 2012, an estimated 35.3 (32.2–38.8) million people were living with HIV (PLHIV) including 3.2 million children. India has the third largest number of PLHIV with estimated number of 2.09 million (2011). Estimated number of children living with HIV (CLHIV) is 1,45,000 and 25,739 such children are on antiretroviral therapy (ART). The prevalence of anemia in these children has a wide range (57% - 100%) as reported by number of researchers. Screening for anemia before initiating ART is recommended as it helps in deciding the composition of the first line ART regimen (Zidovudine based regimen avoided in anemia) and in treatment of anemia. Objectives: To study the clinico-social profile and anemia in Children living with HIV and to assess the effect of ART on anemia. Material & Methods: The study was part of follow up study of children seeking ART in Delhi undertaken between November 2012 and March 2014 in Kalawati Saran Children Hospital and Dr. Ram Manohar Lohia Hospital. It involved a retrospective case review and one year follow up of 55 children between 11 months to 13 years of age living with HIV and attending the pediatric ART clinic. Information on demographic and clinical profile including anemia in CLHIV were studied before and one year after the start of ART. Results: Majority (61.8%) of CLHIV comprised of boys. Fourteen (25.5%) children were orphans. Both parents of CLHIV were found to be positive in 69.1% while mother was found to be positive in 76.4%. Before the start of ART anemia was seen in forty five (81.8%) children out of which thirty four were having moderate to severe anemia, while after one year of ART anemia was seen in twenty (36.3%) children out of which eleven were moderately anemic and no one had severe anemia. There was a significant reduction in prevalence and severity of anemia in children following ART (p=0.00). Conclusion: HIV positive children should be screened for anemia before initiation of ART and should be closely followed up for anemia during ART. There is evidence of reduction in prevalence of anemia following ART.